2018
DOI: 10.5120/ijca2018917748
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining Analysis with Association Rules Method to Determine the Result of Fish Catch using FP-Growth Algorithm

Abstract: This study aims to analyze the data to determine the correlation between fish catch, whether certain fish affect the other fish. Lots of natural resources in Indonesia, especially in the marine sector that can be used one of them are fisheries. Each region has the potential of marine fish species with different numbers and species, this can lead to problems that lack of information on the correlation between fish catch, whether certain fish potentially affect the catch. To overcome this problem, it is necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…Minimum support 50% produces 12 frequent itemsets with itemset of 3. In Table 3, it can be concluded that the greater the minimum support, the fewer the number of items produced [2][7] and the stronger the association relationship between attributes in the rules formed [20]. Table 4, with a minimum support of 10%, it can see the itemsets formed and the items, for ex sample the itemset of four consists of classes or brands PYO, BON, Q BY and YSL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Minimum support 50% produces 12 frequent itemsets with itemset of 3. In Table 3, it can be concluded that the greater the minimum support, the fewer the number of items produced [2][7] and the stronger the association relationship between attributes in the rules formed [20]. Table 4, with a minimum support of 10%, it can see the itemsets formed and the items, for ex sample the itemset of four consists of classes or brands PYO, BON, Q BY and YSL.…”
Section: Discussionmentioning
confidence: 99%
“…Association rule mining is useful for discovering interesting relationships hidden in large data sets [8]. Association rules is data mining processes to find and determine all relationships between items in a database that meet minimum supports and minimum confidence [2]. Association rule is one method that aims to find patterns that often occur among many transactions, where each transaction consists of several items.…”
Section: Association Rulementioning
confidence: 99%
See 2 more Smart Citations
“…The results obtained from the analysis are the greater the minimum support and minimum confidence used, the fewer items and rules are formed. at the minimum support and minimum confidence level with a minimum supply of 50% and minimum confidence of 80%, we can be sure that when YellowFin tuna is obtained it will get Bigeye tuna too [19].…”
Section: Previous Studies On Frequent Pattern Growth (Fp-growth)mentioning
confidence: 99%